Cytoskeletal Protein 4.1R Is a Positive Regulator of the FcεRI Signaling and Chemotaxis in Mast Cells - Draberova, Lubica; Draberova, Helena; Potuckova, Lucie; Halova, Ivana; Bambouskova, Monika; Mohandas, Narla; Draber, Petr (Frontiers in Immunology, 2020)
Protein 4.1R, a member of the 4.1 family, functions as a bridge between cytoskeletal and plasma membrane proteins. It is expressed in T cells, where it binds to a linker for activation of T cell family member 1 (LAT1) and inhibits its phosphorylation and downstream signaling events after T cell receptor triggering. The role of the 4.1R protein in cell activation through other immunoreceptors is not known. In this study, we used 4.1R-deficient (4.1R-KO) and 4.1R wild-type (WT) mice and explored the role of the 4.1R protein in the high-affinity IgE receptor (FcεRI) signaling in mast cells. We found that bone marrow mast cells (BMMCs) derived from 4.1R-KO mice showed normal growth in vitro and expressed FcεRI and c-KIT at levels comparable to WT cells. However, 4.1R-KO cells exhibited reduced antigen-induced degranulation and calcium response. Chemotaxis towards antigen and stem cell factor (SCF) and spreading on fibronectin were also reduced in 4.1R-KO BMMCs, whereas prostaglandin E2-mediated chemotaxis and antigen-induced expression of genes for tumor necrosis factor-α and interleukin-6 were not affected. Antibody-induced aggregation of tetraspanin CD9 inhibited chemotaxis towards antigen in WT but not 4.1R-KO BMMCs, implying a CD9-4.1R protein cross-talk. Further studies documented that in the absence of 4.1R, antigen-mediated phosphorylation of FcεRI β and γ subunits was not affected, but phosphorylation of SYK and subsequent signaling events such as phosphorylation of LAT1, phospholipase Cγ1, phosphatases (SHP1 and SHIP), MAP family kinases (p38, ERK, JNK), STAT5, CBL, and mTOR were reduced. Immunoprecipitation studies showed the presence of both LAT1 and LAT2 (LAT, member 2) in 4.1R immunocomplexes. The positive regulatory role of 4.1R protein in FcεRI-triggered activation was supported by in vivo experiments in which 4.1R-KO mice showed the normal presence of mast cells in the ears and peritoneum, but exhibited impaired passive cutaneous anaphylaxis. The combined data indicate that the 4.1R protein functions as a positive regulator in the early activation events after FcεRI triggering in mast cells.